A Monitoring System for Elderly People Using WiFi Sensing with Channel State Information - Boudlal, Hicham; Mohammed Serrhini; Ahmed Tahiri , (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Healthcare professionals, industry, and academics have all recently expressed a strong interest towards WiFi sensing. These techniques could be used to identify critical occurrences that sensitive persons may suffer, such as falls, sleep abnor-malities, wandering behavior, respiratory illnesses, and irregular heart activity. In this paper, we propose a low-cost, non-intrusive method to remotely monitor el-derly people without deploying devices on their bodies in a given space, using channel state information (CSI) from passive WiFi detection. Specifically, we monitored variables such as sitting and standing activity, and experimental valida-tion in practical situations with variable occupants, various environmental set-tings, and interference from other WiFi devices demonstrates robustness and scalability. Our results suggest that the proposed method can be put into practical-real use to detect activity and alert emergency personnel immediately, providing rapid medical assistance, saving lives, minimizing damage, and reducing anxiety for elderly people residing alone.